Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.37871/jbres1580
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Ginger as Medicine for COVID-19: Literature Study

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) affects other systems, including the digestive, circulatory, urogenital, and even the central nervous systems, as its receptor Angiotensin-Converting Enzyme-2 (ACE-2) is expressed in several organs, such as lungs, intestine, heart, esophagus, kidneys, bladder, testes, liver and brain. Different mechanisms, in particular, massive virus replication, extensive apoptosis and necrosis of lung-related epithelial and endothelial cells, vascular leakage, hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 210 publications
(301 reference statements)
0
2
0
Order By: Relevance
“…It elevates the plasma and bronchial alveolar lavage fluid of patients with severe conditions (48,49). In the study of Utami et al, it was shown that increased production of CXCL1, CXCL2, and CXCL10 in COVID-19 patients can lead to skin lesions and exacerbation of patients' clinical symptoms (50). Additionally, in the study of Carnevale et al, the production of mentioned chemokines can stimulate immune cells and cause skin symptoms in patients (51).…”
Section: Discussionmentioning
confidence: 99%
“…It elevates the plasma and bronchial alveolar lavage fluid of patients with severe conditions (48,49). In the study of Utami et al, it was shown that increased production of CXCL1, CXCL2, and CXCL10 in COVID-19 patients can lead to skin lesions and exacerbation of patients' clinical symptoms (50). Additionally, in the study of Carnevale et al, the production of mentioned chemokines can stimulate immune cells and cause skin symptoms in patients (51).…”
Section: Discussionmentioning
confidence: 99%
“…The NLRP3 inflammasome is highly activated within pulmonary infections, which triggers a severe cytokine storm. Some bioactive compounds extracted from ginger (e.g., gingerols and shogaols) can inhibit NLPR3 inflammasome, which leads to a drastic reduction in cytokine levels, thus preventing the cytokine storm and avoiding many of the consequent symptoms [ 114 ].…”
Section: Zingiber Officinale ( Z Officinale ...mentioning
confidence: 99%